Prolong QTc Interval in Ethionamide-Induced Hypothyroidism in the Treatment of Multidrug Resistant Tuberculosis (MDR TB) - Pratiwi, Dekritiana Dian; Budiono, Eko (Faculty of Medicine Universitas Gadjah Mada, 2023)
Background. Ethionamide, as part of multidrug resistant tuberculosis (MDR TB) treatment, is an antibiotic classified by WHO as a second-line drug with bactericidal property. Administration of ethionamide therapy is associated with the incidence of hypothyroidism in MDR TB patients. The resulting hypothyroidism can be a factor that triggers QTc interval prolongation on electrocardiogram (ECG) during anti-tuberculosis treatmentCase Presentation. A 77-year-old man with a history of pulmonary TB treatment one year ago, returned to undergo the intensive phase of pulmonary TB treatment for two months. Sputum evaluation at the end of the phase showed positive smear results, and the patient was diagnosed with MDR TB after further examination. Before starting MDR TB treatment, an initial ECG examination (QTc interval 0.41 seconds), TSH, and FT4 level were found to be within normal limits. MDR TB regimen including ethionamide 750 mg/day was given for the treatment. In the third month of treatment, the patient was diagnosed with hypothyroidism suspected to be related to ethionamide. In the seventh month of treatment, the patient complained of sudden weakness and QTc interval prolongation in the ECG (0.48 seconds). Ethionamide was stopped and the ECG was evaluated. No QTc interval prolongation was found after stopping ethionamide.Conclusion. This case emphasizes the importance of monitoring side effects arising from anti-tuberculosis treatment, especially ethionamide. Accuracy in diagnosing and following up the side effects of ethionamide administration in MDR TB patients is necessary to prevent worse cardiac events.